Performance of Qualitative and Quantitative Antigen Tests for SARS-CoV-2 Using Saliva - Isao Yokota; Takayo Sakurazawa; Junichi Sugita; Sumio Iwasaki; Keiko Yasuda; Naoki Yamashita; Shinichi Fujisawa; Mutsumi Nishida; Satoshi Konno; Takanori Teshima (MDPI AG, 2021)
The rapid detection of SARS-CoV-2 is critical for the prevention of disease outbreaks. Antigen tests such as immunochromatographic assay (ICA) and chemiluminescent enzyme immunoassay (CLEIA) can yield results more quickly than PCR. We evaluated the performance of ICA and CLEIA using 34 frozen PCR-positive (17 saliva samples and 17 nasopharyngeal swabs [NPS]) and 309 PCR-negative samples. ICA detected SARS-CoV-2 in only 14 (41%) samples, with positivity rates of 24% in saliva and 59% in NPS. Notably, ICA detected SARS-CoV-2 in 5 of 6 samples collected within 4 days after symptom onset. CLEIA detected SARS-CoV-2 in 31 (91%) samples, with a positivity of 82% in saliva and 100% in NPS. These results suggest that the use of ICA should be limited to an earlier time after symptom onset and CLEIA is more sensitive and can be used in situations where quick results are required.